Comparison of Changes in Bone Density and Turnover with Abacavir-Lamivudine versus Tenofovir-Emtricitabine in HIV-Infected Adults: 48-Week Results from the ASSERT Study - Stellbrink, Hans-Jürgen; Orkin, Chloe; Arribas, Jose Ramon; Compston, Juliet; Gerstoft, Jan; Van Wijngaerden, Eric; Lazzarin, Adriano; Rizzardini, Giuliano; Sprenger, Herman G.; Lambert, John; Sture, Gunta; Leather, David; et al. (Clinical infectious diseases, 2010)
Background. Abacavir-lamivudine and tenofovir DF-emtricitabine fixed-dose combinations are commonly used as first-line antiretroviral therapies. However, few studies have comprehensively compared their relative safety profiles. Methods. In this European, multicenter, open-label, 96-week study, antiretroviral-naive adult subjects with human immunodeficiency virus (HIV) infection were randomized to receive either abacavir-lamivudine or tenofovir-emtricitabine with efavirenz. Primary analyses were conducted after 48 weeks of treatment. Bone mineral density (BMD), a powered secondary end point, was assessed by dual energy x-ray absorptiometry. Bone turnover markers (osteocalcin, procollagen 1 N-terminal propeptide, bone specific alkaline phosphatase, and type 1 collagen cross-linked C telopeptide [CTx]) were assessed in an exploratory analysis. Results. A total of 385 subjects were enrolled in the study. BMD loss was observed in both treatment groups, with a significant difference in the change from baseline in both total hip (abacavir-lamivudine group, −1.9%; tenofovir-emtricitabine group, −3.6%; P <; .001) and lumbar spine (abacavir-lamivudine group, −1.6%; tenofoviremtricitabine group, −2.4%; P = .036). BMD loss of ⩾6% was more common in the tenofovir-emtricitabine group (13% of the tenofovir-emtricitabine group vs 3% of the abacavir-lamivudine group had a loss of ⩾6% in the hip; 15% vs 5% had a loss of ⩾6% in the spine). Bone turnover markers increased in both treatment groups over the first 24 weeks, stabilizing or decreasing thereafter. Increases in all markers were significantly greater in the tenofovir-emtricitabine treatment group than in the abacavir-lamivudine group at week 24. All but CTx remained significantly different at week 48 (eg, osteocalcin: abacavir-lamivudine group, +8.07 mg/L; tenofoviremtricitabine group, +11.92 mg/L; P < .001). Conclusions. This study demonstrated the impact of first-line treatment regimens on bone. Greater increases in bone turnover and decreases in BMD were observed in subjects treated with tenofovir-emtricitabine than were observed in subjects treated with abacavir-lamivudine.